Determinants of Contraceptive Uptake among Secondary School Adolescent Girls between 10-19 Years Living In Teso- North, Busia County - Makokha, Emmanuel Oduory (JOOUST, 2023)
Contraceptives are devices, drugs, agents, sexual practices, or surgical procedures that prevent a woman of reproductive age from getting pregnant. There are 58.4% of the adolescent girls in Kenya who use any form of contraception, with 43.8% unmet need of contraception. Busia County is ranked the least contraceptive prevalence rate of 18.6% among adolescent girls aged 10 -19 years in Kenya. Low use of contraceptives leads to high rates of teenage pregnancy leading to early marriages, school dropouts, unsafe abortions and STIs among adolescent girls and youths in the region. Several Non- Governmental Organizations came up with strategies but all were in vain. The main objective of this study was to establish the determinants of contraceptive uptake among secondary school adol escent girls aged 10-19 years in Teso North and research questions were; what are the socio-demographical, knowledge and informational, and quality of reproductive health services determinants to contraceptive uptake among secondary school adolescent girls aged 10-19 years living in Teso North. This study applied mixed method cross-sectional study design and it had 415 respondents who were secondary school adolescent girls in Teso North Sub County for data collection. Qualitative data was collected by conducting two Focused Group Discussions (FGDs) using interview guide. Data analysis was done by computer software statistical Package for Social Scientists (SPSS) version 25. Analysis methods used were descriptive and inferential statistics comprising of chi -squares and binary logistic regression analysis to identify determinants of contraceptive uptake among adolescent girls. Odds ratios, 95% confidence intervals and p-values were reported. P-values <0.05 and below were considered statistically significant. This study established that 47.2 % (196) of the girls had sexual partners, 72.4 % (301) knew at least a contraceptive method and 29.3 %( 122) of them had used a contraceptive method. It revealed that, the class (Form 4s were nine times likely to use contrace ption compared to Form 1s (AOR 8.9, 95%CI 2.0 - 39.7, P = 0.004), residence (girls from the peri-urban residence were nine times likely to use contraception compared to those from rural residence (AOR 9.0, 95%CI 2.8 - 28.9, P<0.0001), staying with guardians was three times likely to use contraception compared to staying with parents (AOR 2.7, 95%CI 1.2 - 6.1, P = 0.018), having a sexual partner was sixteen times likely to use contraception compared to lack of partner (AOR 16.4, 95%CI 5.8 - 46.6, P<0.0001), discussing contraceptives with anyone was four times likely to use contraception compared to keeping to themselves (AOR 4.2, 95%CI 1.7 - 10.7, P = 0.002), ability to access contraception/ sexual reproductive services at any time at home or school was three times likely to use contraception compared to unable to access (AOR 3.4, 95%CI 1.3 - 9.2, P = 0.016) and knowing a place in the community where one can get contraceptives was five times likely to use contraception compared to failure to know a place in community (AOR 4.9, 95%CI 1.3 - 17.9, P = 0.017) were significant determinants for contraceptive uptake. Contraceptive uptake among the secondary school adolescent girls in Teso North was 29.3%, despite half of the girls being sexually active. The key recommendations based on the study findings; the county government of Busia, ministry of health directorate should collaborate with available partners and the media houses to promote use of contraception using media channels like television, radios and community opinion leaders. Other health care providers should reach out to the people, targeting rural settings to offer sexuality health education on healthy birth spacing, addressing myths and misconceptions surrounding contraception. The parents should always be open and available by creating time to discuss adolescent health matters with their children as per age appropriate comprehensive sexuality education. All the public health facilities should make the adolescent Sexual Reproductive Health services easily accessible to all the people without discrimination of their age, gender, marital status or parity.
Keywords: Contraceptive